1995
DOI: 10.1002/bjs.1800821036
|View full text |Cite
|
Sign up to set email alerts
|

High morbidity rate after converted laparoscopic colorectal surgery

Abstract: Sixteen of 65 laparoscopically assisted colorectal operations were converted to an open procedure, usually because of dissection difficulties. Conversion was decided early in the procedure in four cases without perioperative morbidity and later in 12 cases, after a mean of 56 min. The results in patients undergoing converted operation were compared with those in 252 having a planned open colorectal procedure during the same period. The groups were comparable with regard to age, health status, factors influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
6
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 17 publications
2
50
6
11
Order By: Relevance
“…Likewise, reported incidences of anastomosis leakage are 2.4-6.8% after open surgery, 2.7% after laparoscopy, but 25% after conversion. 25,31 However, in our study, anastomosis leakage was observed in laparoscopy and open surgery groups but not in the conversion group. In conversion patients, the incidence of mortality is reported to be 3.5%.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…Likewise, reported incidences of anastomosis leakage are 2.4-6.8% after open surgery, 2.7% after laparoscopy, but 25% after conversion. 25,31 However, in our study, anastomosis leakage was observed in laparoscopy and open surgery groups but not in the conversion group. In conversion patients, the incidence of mortality is reported to be 3.5%.…”
contrasting
confidence: 69%
“…When the outcomes of patients undergoing laparoscopy or conversion surgery are compared, a higher rate of morbidity is seen in both groups compared to those having open surgery, according to the literature. 25 While no difference in terms of morbidity and mortality are reported between conversion patients and the open surgery group in this report, another study reports a higher complication rate and a longer period of hospitalization in conversion patients compared to those having laparoscopy or open surgery. 8,26 The morbidity rate is reported as 23% after laparoscopy, 11-20% after open surgery, and 35.2% after conversion.…”
contrasting
confidence: 58%
“…In general, higher complication rates have been noted in patients that required conversions during laparoscopic cholecystectomy, appendectomy and colectomy as compared to the open approach [31][32][33][34]. However, Slim et al [35] found that while the conversion generally resulted in an inferior outcome compared to that reported for open colorectal surgery, none of the patients who underwent a conversion at an early stage experienced a complicated postoperative course. Their findings conclusively demonstrate that an early decision to abandon the laparoscopic approach is the key to avoiding serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprising, studies found longer operating times and higher risk of conversion with associated morbidity. [37][38][39][40] However, with increased laparoscopic experience, refinement in technique, and advances in surgical technology, the indications broadened. Laparoscopic resection was demonstrated to be feasible and safe in recurrent uncomplicated disease.…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%